Sex differences in heart failure - Eisenberg, Evann; Di Palo, Katherine E.; Piña, Ileana L. (Clinical cardiology (Mahwah, N.J.), 2018)
Heart failure (HF) numbers continue to grow in the United States and approximately 50% of patients living with HF are women. For the provider, it is critical to understand the role that gender plays in recognition, diagnosis, and management. The purpose of this literature review is to highlight the prevalence of heart failure in women and discuss gender variations in epidemiology, symptoms, pharmacology, and treatment as well as examine the representation of women in clinical trials.